Pengaruh rekrutmen dan motivasi pada PT Secm Tech Indonesia terhadap kinerja karyawan proyek Mechanical, Electrical, Plumbing (MEP) - Putra, Thomas Erdian; Wibowo, Wijanarko Agus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to examine the influence of recruitment and motivation at PT Secm Tech Indonesia on the performance of Mechanical, Electrical, Plumbing (MEP) project employees. The method in this study uses a quantitative approach with statistical data analysis. Data were obtained through a Likert scale questionnaire 1–5, then analyzed using an inferential approach to determine the influence between variables. The population of this study was all MEP project workers at PT Secm Tech Indonesia, with a sample of 195 respondents determined through a proportional random sampling method. Data were analyzed using multiple linear regression methods processed with the help of SPSS software version 27. Based on the results of data analysis, this study shows that recruitment partially has a significant effect on employee performance, with a t-value of 0.783 and a significance of 0.023 (<0.05). Motivation also has a significant effect partially on employee performance, indicated by a t-value of 1.656 and a significance of 0.009 (<0.05). Simultaneously, recruitment and motivation significantly influence employee performance, as evidenced by an F-value of 11.560 and a significance level of 0.000 (<0.05). These two variables explain 52.3% of the variation in employee performance, while the remaining 47.7% is influenced by other factors.